The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1007/bf00223647
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a wild-type GBSS gene introduced into an amylose-free potato mutant by Agrobacterium tumefaciens and the inheritance of the inserts at the microsporic level

Abstract: Granule-bound starch synthase (GBSS) catalyses the synthesis of amylose in starch granules. Transformation of a diploid amylose-free (amf) potato mutant with the gene encoding GBSS leads to the restoration of amylose synthesis. Transformants were obtained which had wild-type levels of both GBSS activity and amylose content. It proved to be difficult to increase the amylose content above that of the wild-type potato by the introduction of additional copies of the wild-type GBSS gene. Staining of starch with iod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
4
18
0
Order By: Relevance
“…A decreased amylose content in potato starch can be obtained by mutation in the GBSS gene such as in the amf mutant [9] or by introduction of antisense genes coding for GBSS [34]. Indications for a third possibility were found during complementation studies of the amf mutant with a wild-type GBSS gene of potato [18,2]. When complementing the potato amfmutant, transformants were found with full and partial complementation.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…A decreased amylose content in potato starch can be obtained by mutation in the GBSS gene such as in the amf mutant [9] or by introduction of antisense genes coding for GBSS [34]. Indications for a third possibility were found during complementation studies of the amf mutant with a wild-type GBSS gene of potato [18,2]. When complementing the potato amfmutant, transformants were found with full and partial complementation.…”
Section: Introductionmentioning
confidence: 87%
“…In the present study, a partially complemented amf mutant was crossed with a wild-type potato, in order to investigate the effect of co-suppression on complementation in the presence of an endogenous wild-type GBSS allele. In parallel with the complementation experiments [2], the cloned wild-type GBSS gene was introduced in a wild-type potato genotype. The characteristics of these transgenic plants and those resulting from transformation with other GBSS sequences will be outlined.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that a further increase in phosphate content is only possible when more places are available to deposit phosphate groups in the starch granules resulting from a change in the starch molecular structure. A similar phenomenon has been observed in earlier studies, demonstrating that introduction of additional copies of the granule-bound starch synthase (GBSS) gene into potato plants did not increase amylose content above the wild-type level (Flipse et al, 1994;Flipse et al, 1996a). The authors reasoned that the restricted amount of amylose content was due to the limited space existed to deposit amylose molecules in starch granules.…”
Section: Discussionsupporting
confidence: 74%
“…This is supported by the earlier studies, showing elongated and branched chains are preferably phosphorylated (Blennow et al, 2002;Schwall et al, 2000;Takeda and Hizukuri, 1982). A similar phenomenon has been observed in transgenic potato plants overexpressing the granule-bound starch synthase (GBSS) gene (Flipse et al, 1994;Flipse et al, 1996a). The authors found that the amylose content in transformants did not increase above the wild-type level, therefore, they suggested that there is limited space existing in starch granules to deposit amylose molecules.…”
supporting
confidence: 71%
“…Extensive studies aimed at controlling the quality of starch in potato tubers have been performed . Transformation of the amylose-deficient amf mutant of potato with the GBSS gene led to amylose synthesis (van der Leij et al 1991, Flipse et al 1994, whereas various levels of reduction in GBSS protein and amylose were observed in transgenic potato tubers with the antisense GBSS gene connected to the CaMV35S promoter or GBSS promoter , Salehuzzaman et al 1993, Kuipers et al 1994, Kuipers et al 1995. The role of AGPase in starch accumulation (Muller-Rober et al 1992, Stark et al 1992) and the functions of soluble starch synthesis and starch branching enzyme (Flipse et al 1996, Kortstee et al 1996, Jobing et al 1999 have been investigated by the use of sense and antisense genes in transgenic potatos.…”
Section: Introductionmentioning
confidence: 99%